Penerapan Algoritma Salsa20 Untuk Mengamankan Sandi Akun Virtual - Hasibuan, Muhammad Abdul Rasyid; Sinurat, Sinar (LPPM UNIKA Santo Thomas Medan, 2024)
The application of the SALSA20 algorithm in securing virtual account passwords aims to increase the security of users' personal data in an increasingly complex digital era. The SALSA20 algorithm, which is known as one of the efficient and secure stream cipher algorithms, has superior characteristics in terms of speed and resistance to cryptanalysis attacks. This research explores the implementation of SALSA20 in a virtual account password security system, testing the performance of this algorithm under various conditions and comparing it with other commonly used cryptographic algorithms, such as AES (Advanced Encryption Standard). The research results show that SALSA20 is able to provide a high level of security with a faster execution time compared to several other algorithms. Testing includes analysis of encryption and decryption speed, system resource usage, as well as resistance to various types of attacks, such as brute force and differential analysis attacks. In addition, the integration of SALSA20 in real applications shows that this algorithm is easy to implement and provides significant protection against attempts to steal user passwords and personal data.